Pengorbanan Yesus Kristus di Kayu Salib Sebagai Bukti Penebusan Dosa Manusia dan Relevansinya Bagi Orang Percaya Masa Kini - Desi Sriyanti Tonis; Desti Meliana Mangngi Kale; Malik Bambangan (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This article discusses Jesus Christ's sacrifice on the cross as evidence of human atonement and its relevance to believers today. From the perspective of Christian faith, this event is considered a central point in the history of salvation, demonstrating divine grace and justice. Through a search of the meaning of Christ's sacrifice, this article provides a broad understanding of the meaning of Christ's suffering for man's atonement and explains how Christ's sacrifice is concrete evidence of unconditional love and the divine will to blot out human sin. Through the analysis of the meaning of redemption worked out by Jesus Christ, which will expand the theoretical basis of the purpose of Jesus' sacrifice on the cross. This article also provides a theory of the importance of understanding Christ's sacrifice on the cross, thus becoming a reference for believers in terms of faith and belief that through Christ's sacrifice brings redemption to believers. Meanwhile, the relevance of Christ's sacrifice on the cross will also affect several aspects of the believer's life, namely in terms of faith, confession, and holy living. In writing this article, a qualitative approach method is used with a literature study method. The search for the meaning of Christ's sacrifice can be studied from several perspectives, namely the theological perspective, the moral perspective and the psychologist's perspective. From a theological perspective, Christ's sacrifice is a form of God's love for man, so He sent His Son, Jesus Christ, as a sacrifice to redeem believers. So that the work of salvation done by Jesus Christ leads to a victory for believers because they have been redeemed and freed from the power of death, and also becomes a means of improving the relationship between man and God. From a moral perspective, it can be understood that Christ's sacrifice on the cross is an example of sacrifice and an example of love for believers. Thus, this article contributes to the understanding of Christ's sacrifice on the cross as a form of human atonement, and enriches the spiritual life of believers and strengthens faith, motivates spiritual life, and clarifies the moral principles underlying the Christian life.